2006
DOI: 10.1007/s11010-006-9196-5
|View full text |Cite
|
Sign up to set email alerts
|

The Activities of Antioxidant Enzymes and the Level of Malondialdehyde in Cerebellum of Rats Subjected to Methotrexate: Protective Effect of Caffeic Acid Phenethyl Ester

Abstract: Methotrexate (MTX), a folic acid antagonist, is widely used as a cytotoxic chemotherapeutic agent. MTX-associated neurotoxicity is an important clinical problem. The aim of this study was to investigate the role of caffeic acid phenethyl ester (CAPE) on cerebellar oxidative stress induced by MTX in rats. A total of 19 adult male rats were divided into three experimental groups as follows: MTX group (MTX treated), MTX+CAPE group (MTX+CAPE treated), and control group. MTX was administered intraperitoneally (i.p.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
53
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(62 citation statements)
references
References 39 publications
6
53
0
3
Order By: Relevance
“…Experimental studies have demonstrated the increased production of oxygen free radicals following MTX treatment, and these free radicals may lead to mitochondrial functional impairment [11]. MTX-induced toxicity is characterized by activation of the in ammatory response and signi cantly increased production of pro-in ammatory cytokines [29]. MTX-induced renal damage is further exacerbated by subsequent neutrophil in ltration and oxidative stress contribute [13].…”
Section: Discussionmentioning
confidence: 99%
“…Experimental studies have demonstrated the increased production of oxygen free radicals following MTX treatment, and these free radicals may lead to mitochondrial functional impairment [11]. MTX-induced toxicity is characterized by activation of the in ammatory response and signi cantly increased production of pro-in ammatory cytokines [29]. MTX-induced renal damage is further exacerbated by subsequent neutrophil in ltration and oxidative stress contribute [13].…”
Section: Discussionmentioning
confidence: 99%
“…Group 2: MTX group (n=7): A single dose of 20 mg/kg of MTX was administered I.P. Because, it was revealed in previous studies that this dose (20 mg/kg) causes tissue toxicity [19] . MTX was dissolved in physiological saline.…”
Section: Groupmentioning
confidence: 99%
“…Uzar et al (27) reported that CAPE significantly reduced the activities of antioxidant enzymes and the level of malondialdehyde in the cerebellum of rats subjected to methotrexate. Ginis et al (13) reported that pretreatment with CAPE might protect brain tissue against ifosfamide-induced central neurotoxicity.…”
mentioning
confidence: 99%